The effect of democracy on good governance in emerging economies - Efeoğlu, Rabia (Gazi Publishing, 2022)
The aim of the study is to analyze the impact of democracy on good governance in the period from 2002 to 2018 for emerging market economies. Good governance is determined by six basic indicators which are good governance, accountability, political stability, government efficiency, quality of regulations, rule of law, and prevention of corruption. The democracy index is an independent variable and the highest value of the index is 1 and the lowest value is 7. Static panel data analysis method was used in this study. According to the findings, the effect of democracy index on good governance is negative and statistically significant. As democracy increases in emerging market economies, so does good governance. When the studies about democracy and good governance are examined, it is generally seen that, there are more studies investigating the relationship between democracy and economic growth and development as well as the relationship between good governance and sustainable economic development and economic growth. However, it can be said that studies investigating the relationship between democracy and good governance are limited in numbers and there are less empirical studies than theoretical studies. For this reason, it was decided to make an empirical study on the effect of democracy on good governance in order to fill this gap in the literature and to contribute to the literature.

Çalışmanın amacı, yükselen piyasa ekonomileri için 2002-2018 döneminde demokrasinin iyi yönetişim üzerindeki etkisini analiz etmektir. İyi yönetişim, altı temel iyi yönetişim göstergesi olan hesap verebilirlik, politik istikrar, hükümetin etkinliği, düzenlemelerin kalitesi, hukukun üstünlüğü, yolsuzluğun önlenmesinin ortalaması alınarak belirlenmiştir. Demokrasi endeksi bağımsız değişkendir ve endeksin en yüksek değeri 1, en düşük değeri 7’dir. Çalışmada statik panel veri analiz yöntemi kullanılmıştır. Elde edilen bulgulara göre demokrasi endeksinin iyi yönetişim üzerindeki etkisi negatif ve istatistiki bakımdan anlamlıdır. Yükselen piyasa ekonomilerinde demokrasi arttıkça iyi yönetişim de artmaktadır. Demokrasi ve iyi yönetişim çalışmaları incelendiğinde genel olarak demokrasinin ekonomik büyüme ve kalkınmayla ilişkisinin, iyi yönetişimin ise sürdürülebilir ekonomik kalkınma ve ekonomik büyüme ile ilişkisinin araştırıldığı çalışmaların yoğunlukta olduğu görülmektedir. Ancak demokrasi ve iyi yönetişim arasındaki ilişkinin araştırıldığı çalışmaların sınırlı sayıda olduğu ve bu konuda ampirik çalışmaların teorik çalışmalardan daha az olduğu söylenebilir. Bu sebeple literatürdeki söz konusu boşluğu doldurmak ve literatüre bir katkı adına demokrasinin iyi yönetişim üzerine etkisine yönelik bir ampirik çalışma yapmaya karar verilmiştir.
Keywords: Economics; İyi yönetişim; Demokrasi; Yükselen ekonomiler; Good governance; Democracy; Emerging economies; Ekonomi; 8. Economic growth; 1. No poverty; 16. Peace & justice